Gerakan Kolaborasi Pemberdayaan Kader TP Posyandu di Desa Cikakak : mewujudkan lansia potensial dalam meningkatkan nilai gaya hidup slow living Banyumas - Titi Rahmawati; Isran Kamal; Shinta Julianti; M. Musa Al Hasyim; Dimas Purbo Pambudi; Muhammad Riyan Fitria Ramdlani; Resya Nur Intan Putri; Suci Lestari; Arif Muhamad Nurdin (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Health support for the elderly by the Integrated Service Post (Posyandu) is an effort to increase the capacity of the elderly. There are 9-13 posyandu cadres at the RW level, and with a total of 6 Posyandu, the number reaches 63 cadres, of which 25 are skilled cadres in Cikakak Village. The general goal of the Posyandu is to improve the health status of the elderly in order to achieve a happy and functional old age in family and community life. This condition is in line with the collaborative empowerment program which aims to improve the quality of life of young elderly at the age of 60-69 years who dominate the structure of the elderly in Cikakak Village, Banyumas by forming the knowledge and skills of cadres as providers of physical and mental health services for the elderly. We used a qualitative approach with interview guidelines and questionnaires for observation in a phenomenological approach. The results of the study show that the collaborative movement of posyandu cadres in improving the quality of life of the elderly can be improved through service interventions, especially by designing treatment programs that focus not only on diseases but also on overall well-being, including mental health; and maximizing the empowerment of the elderly by identifying areas that need improvement to achieve a better quality of life. The next collaboration on the empowerment of posyandu cadres is the first step to increase the capacity of the elderly and the application of science in the form of technological innovation to create potential elderly who apply a slow living lifestyle, namely a simple and meaningful life. One of the technological innovations that supports mental health and has been modified according to the needs of the elderly in maximizing peer counseling programs with early detection of stress levels is Galvanic Skin Response (GSR-Pro) which is proven to have an accuracy of up to 80% in reading the stress level of the elderly in Cikakak Village, Banyumas.